The right amount of trust - Jeffrey Butler; Paola Giuliano; Luigi Guiso (Institute for the Study of Labor (IZA), 2009)
A vast literature has investigated the relationship between trust and aggregate economic performance. We investigate the relationship between individual trust and individual economic performance. We find that individual income is hump-shaped in a measure of intensity of trust beliefs available in the European Social Survey. We show that heterogeneity of trust beliefs in the population, coupled with the tendency of individuals to extrapolate beliefs about others from their own level of trustworthiness, could generate the non-monotonic relationship between trust and income. Highly trustworthy individuals think others are like them and tend to form beliefs that are too optimistic, causing them to assume too much social risk, to be cheated more often and ultimately perform less well than those who happen to have a trustworthiness level close to the mean of the population. On the other hand, the low-trustworthiness types form beliefs that are too conservative and thereby avoid being cheated, but give up profitable opportunities too often and, consequently, underperform. Our estimates imply that the cost of either excessive or too little trust is comparable to the income lost by foregoing college. Furthermore, we find that people who trust more are cheated more often by banks as well as when purchasing goods second hand, when relying on the services of a plumber or a mechanic and when buying food. We complement the survey evidence with experimental evidence showing that own trustworthiness and expectations of others' trustworthiness in a trust game are strongly correlated and that performance in the game is hump-shaped.
urn:nbn:de:101:1-200910122570
Keywords: A1; A12; D1; O15; Z1; 330; Trust; trustworthiness; economic performance; culture; false consensus; Kulturpsychologie; Wirtschaftslage; Soziale Lage; Vertrauen; Risikopräferenz; EU-Staaten